Moradia social : ocupação de espaços desconstruídos livres - Monteiro, Luzia Cristina Antoniossi (Universidade Federal de São Carlos, 2009)
The issue of social housing interest is disturbing. It is a serious problem of spatial social juridical nature, promoter of segregation and lack of citizenship. In Brazilian cities a paradox was found: there are millions of people who are homeless while there are many millions of unoccupied dwellings. Thus, while families suffer from lack of shelter, there are deconstructing homes. These properties do not meet the stranded social function of property advocated by the Federal Constitution of 1988. There is a new urban juridical order that is consolidated with the advent of the Statute of the City and provides the occupation of those free deconstructed spaces as a way to minimize the current housing demand. The study's main objective is to analyze the possibility of occupation of free constructed spaces through the implementation of legal instruments existing in the legislation as a means of mitigating the housing problems. The legal instruments and procedures must be applied in cities, observing the peculiarities and municipal laws. Action research was conducted in Sertãozinho-SP as an example of an average town in the state that has consolidated a social movement for over 20 years, promoting occupations for housing purposes.
Keywords: Engenharia urbana; Habitação popular; Função social da propriedade; Desconstrução espacial; Movimentos sociais; Posse da terra; ENGENHARIAS